Preliminary Exploration of the Sequence of Nerve Fiber Bundles Involvement for Idiopathic Normal Pressure Hydrocephalus: A Correlation Analysis Using Diffusion Tensor Imaging - Huang, Wenjun; Fang, Xuhao; Li, Shihong; Mao, Renling; Ye, Chuntao; Liu, Wei; Lin, Guangwu (Frontiers in Neuroscience, 2021)
The study preliminarily explored the sequence and differences in the involvement of different neuroanatomical structures in injury tolerance in idiopathic normal pressure hydrocephalus (INPH). We retrospectively analyzed the differences in DTI parameters in 15 ROIs (including the bilateral centrum semiovale (CS), corpus callosum (CC) (body, genu and splenium), head of the caudate nucleus (CN), internal capsule (IC) (anterior and posterior limb), thalamus (TH), and the bilateral frontal horn white matter hyperintensity (FHWMH)) between 27 INPH patients and 11 healthy controls and the correlation between DTI indices and clinical symptoms, as evaluated by the INPH grading scale (INPHGS), the Mini-Mental State Examination (MMSE) and the timed up and go test (TUG-t), before and 1 month after shunt surgery. Significant differences were observed in DTI parameters from the CS (pFA1 = 0.004, pADC1=0.005) and the genu (pFA2 = 0.022; pADC2=0.001) and body (pFA3=0.003; pADC3=0.002) of the CC between the groups. The DTI parameters from the CS were strongly correlated with the MMSE score both preoperatively and postoperatively. ADC values of anterior and posterior limbs of the IC were also correlated with MMSE. The DTI parameters of the head of the CN were correlated with motion, and the ADC value was significantly correlated with the MMSE score. The FA value from TH correlated with an improvement in urination after shunt surgery. Our results indicated that different neuroanatomical structures are affected to different degrees by diseases due to their positions in neural pathways and characteristics; this can affect the prognosis of shunt surgery.